Oxidative Stress and Bipolar Mood Disorder: An Important Yet Ambiguous Relationship - Sara Rahsepar; Amirhooshang Mohammadpour (Research Center for Rational Use of Drugs (RCRUD), 2021)
Bipolar disorder is a chronic psychological condition that disturbs many patients' lives around the world. The exact pathophysiology of bipolar disorder is yet unknown, but there are several hypotheses to explain this condition. One of the most challenging theories is the role of oxidative stress in the progression of bipolar disorder. Here, we conducted a narrative review to gather the studies that investigated the relationship between bipolar disorder and oxidative stress. We searched PubMed, Scopus, Web of science, and google scholar databases using the following keywords: "bipolar disorder," "oxidative stress," "oxidative markers," and "bipolar patients."     A majority of studies showed that oxidative markers such as Thiobarbituric acid reactive substances are significantly higher in bipolar patients compared to healthy subjects. Based on the included articles, bipolar disorder is associated with oxidative stress. Nevertheless, further well-established Cohorts are required to support these results.